2020
DOI: 10.1080/21681805.2020.1798501
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumour associated trypsin inhibitor, as a biomarker for survival in renal cell carcinoma

Abstract: Objective: Tumour associated trypsin inhibitor (TATI) is a peptide that is a marker for several tumours. TATI may also behave as an acute phase reactant in severe inflammatory disease. Overexpression of TATI predicts an unfavourable outcome for many cancers. This study aimed to evaluate the prognostic value of pre-and postoperative concentration of TATI in serum (S-TATI) of patients with renal cell carcinoma (RCC). Materials and methods: S-TATI was determined by time resolved immunofluorometric assay in preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…However, we observed that elevated S-TATI appears to function as an independent prognostic biomarker in OPSCC ( Table 2 ). Similar results were observed in other malignancies [ 28 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, we observed that elevated S-TATI appears to function as an independent prognostic biomarker in OPSCC ( Table 2 ). Similar results were observed in other malignancies [ 28 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Numerous meta-analyses (e.g., [7][8][9]) have tried to identify the gene biomarkers whose altered sequence and/or expression may serve to diagnose the KC form, and whose restoration may help to cure it. Among others, the 27.0 release (29 October 2020) of the Genomic Data Commons Data Portal [10] includes 59,612 mutations detected in 20,426 genes sequenced from 3295 (2110 male and 1185 female) KC cases.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous meta-analyses (e.g. : [7][8][9]) tried to identify the gene biomarkers whose altered sequence or/and expression may serve to diagnose the kidney cancer form, and whose restoration may help to cure it. Among others, the 26.0 release (September 08, 2020) of the Genomic Data Commons Data Portal [10] 2.67%) were mutated in more than 2% of cases.…”
Section: Introductionmentioning
confidence: 99%